Student-Run Clinics Adapt to Emerging Changes in Healthcare and Education - Coburn, Brian; Seryak, Katie; Lander, Jessica (Journal of Student-Run Clinics, 2016)
Healthcare and medical education have undergone rapid evolution in the past five years. These changes highlight the flexibility and impact of student-run clinics (SRCs). From the passage of the Affordable Care Act to medical education’s increasing emphasis on healthcare delivery and experiential learning, the rise of SRCs has placed students on the front lines of progress. During this time, the Society of Student-Run Free Clinics (SSRFC) has worked diligently to help clinics adapt and prosper in this new era. In this article we reflect on the upcoming SSRFC Annual Conference and how SRCs are situated to adapt to these recent changes. We conclude by identifying specific SSRFC goals to help students and clinics continue to grow.